Quadratic functions in additional mathematics and mathematics: an analysis on students' errors / Teh Faradilla Abdul Rahman and Mohammad Sharmizie Mohamad Foad - Abdul Rahman, Teh Faradilla; Mohamad Foad, Mohammad Sharmizie (2021)
Mathematics calculation errors made by students are the common mistakes found in any mathematics class. In some cases, these frequent mistakes could contribute to loss of interest in mathematics and discourage the students to achieve the expected level of thinking skills. Mathematics and Additional Mathematics are two related subjects with some students might find Additional Mathematics is more challenging than Mathematics. However, a group of students might think the opposite way or might say the two subjects have the same level of challenges. It is interesting to discover if the students' achievements in one subject have any relation with the other. Therefore, the objective is to make an error analysis of quadratic functions in Additional Mathematics and Mathematics. Next, to identify how students' achievements in Additional Mathematics quadratic functions relates to their achievements in Mathematics quadratic functions. This study used mixed approaches which involve interviews and mathematics written test conducted with the students. There were 40 secondary school students participated in this study. The analysis of the errors from written test was analyzed based on Newman Error Hierarchical Model whereas the descriptive analysis and Pearson correlation were conducted using Statistical Package for Social Science (SPSS). Overall, the outcomes indicated that errors committed mostly by students are process skill error, comprehension error and carelessness error. Other than that, a statistically significant difference was found in errors made by students between Additional Mathematics and Mathematics. Moreover, there also showed a positive and low correlation between students' performances in quadratic functions in both subjects. Future studies are recommended to explore error usually committed by students especially those who are underperformed in mathematics.